Вычислить:
$$12. \frac{2\frac{5}{8} - \frac{2}{3} \cdot 2\frac{5}{14}}{(3\frac{1}{12} + 4,375) : 19\frac{8}{9}}.$$

Решение:
\(12. \frac{2\frac{5}{8} - \frac{2}{3} \cdot 2\frac{5}{14}}{(3\frac{1}{12} + 4,375) : 19\frac{8}{9}} = 2\frac{17}{21}.\)

\(
1) \frac{2}{3} \cdot 2\frac{5}{14} = \frac{2}{3} \cdot \frac{33}{14} = \frac{2 \cdot 33}{3 \cdot 14} = \frac{1 \cdot 11}{1 \cdot 7} = \frac{11}{7} = 1\frac{4}{7};
\)

\(
2) 2\frac{5}{8} - 1\frac{4}{7} = 2\frac{35}{56} - 1\frac{32}{56} = 1\frac{3}{56};
\)

\(
3) 3\frac{1}{12} + 4,375 = 3\frac{1}{12} + 4\frac{375}{1000} = 3\frac{1}{12} + 4\frac{3}{8} = 3\frac{2}{24} + 4\frac{9}{24} = 7\frac{11}{24};
\)

\(
4) 7\frac{11}{24} : 19\frac{8}{9} = \frac{179}{24} : \frac{179}{9} = \frac{179}{24} \cdot \frac{9}{179} = \frac{179 \cdot 9}{24 \cdot 179} = \frac{1 \cdot 3}{8 \cdot 1} = \frac{3}{8};
\)

\(
5) 1\frac{3}{56} : \frac{3}{8} = \frac{59}{56} \cdot \frac{8}{3} = \frac{59 \cdot 8}{56 \cdot 3} = \frac{59 \cdot 1}{7 \cdot 3} = \frac{59}{21} = 2\frac{17}{21}.
\)
Ответ: \(2\frac{17}{21}.\)

Добавить комментарий


Защитный код
Обновить

Возможно, Вам нужно вот это: